Reducing Cardiovascular Risk in the Diabetic Community: A Screening and Counseling Program at Talise Health Centre - Nurmalisa, Baiq Emy; Pangaribuan, Helena; Evita, Evita (Jurnal Pengabdian Masyarakat Lentora, 2025)
Background: Noncommunicable diseases, particularly cardiovascular disease (CVD) and diabetes mellitus (DM), pose a significant global and national health burden. Patients with DM face a 2-4 times higher risk of CVD, the leading cause of mortality in over 65% of this population. Despite this, awareness and integrated screening for CVD risk among DM patients in primary healthcare settings, such as the Talise Health Center, remain limited. This community service initiative was designed to address this gap by implementing a comprehensive screening and personalized education program. Objective: This community service initiative aimed to detect CVD risk and provide targeted education to DM patients in the work area of the Talise Health Center. Methods: Methods: The activity was conducted on June 3, 2025, with 30 DM patients. The method involved a three-step process: (1) Screening of blood pressure, BMI, blood glucose, and cholesterol, with results plotted on the WHO/ISH risk prediction chart to stratify participants into low, moderate, or high 10-year CVD risk categories; (2) An educational session, comprising a pre-test, personalized counseling based on risk category, and a post-test to evaluate knowledge retention; (3) Dissemination of educational booklets and banners for sustained learning.Results: Screening revealed that 20 participants (66.7%) had low CVD risk, 9 (30.0%) had moderate risk, and 1 (3.3%) had high risk. The educational intervention was successful in reinforcing knowledge. The average knowledge score was increased at a high level (Pre-test score: 42,5.1% ± 10.2 vs. Post-test score: 82.0% ± 9.8).Conclusion and Suggestion: The finding that over one-third of screened DM patients were at moderate-to-high CVD risk underscores the critical need for integrated screening in primary care. Personalized counseling effectively maintained patient knowledge. It is strongly recommended that the Talise Health Center integrates routine CVD risk screening for all DM patients and continues providing targeted education to mitigate long-term cardiovascular complications.